Feasibility of financing nature-based solutions for water security through water tariffs: Evidence from South Africa - Nicola S. du Plessis; Jane K. Turpie; Gwyneth K. Letley (Aqua, 2024)
In many countries, catchment restoration is underfunded. This study aims to address whether household water pricing could be used as a mechanism for securing funds for catchment restoration. The objectives were to determine households' willingness to pay (WTP) for their existing water use, investigate whether institutional trust and municipal satisfaction influenced WTP, and establish whether aggregate consumer surplus at the municipal scale could cover the costs needed to finance catchment restoration. Surveys were conducted on 502 households in three metropolitan municipalities in the City of Cape Town, eThekwini, and Nelson Mandela Bay. Contingent valuation revealed that average WTP for water was between 12 and 137% more and 32 and 73% more than what households currently pay for water per month in the City of Cape Town and eThekwini, respectively. Satisfaction with municipal service delivery positively influenced WTP, while institutional trust did not. The City of Cape Town, based on the aggregate WTP from the higher income categories, consumer surplus was 779 million South African Rand (ZAR)/year, more than double the estimated cost required to restore the catchment areas supplying water to the city over 30 years. In eThekwini, consumer surplus was equal to the amount needed over 30 years (250 million ZAR/year). These results demonstrate the significant potential to raise water tariffs for higher income households in metropolitan municipalities. HIGHLIGHTS Domestic water users in two metropolitan municipalities were willing to pay significantly more for their water than current prices.; This consumer surplus could cover a significant proportion of the costs required to restore catchment areas.; In the third municipality, willingness to pay was lower as a result of low satisfaction with service delivery.; Generating finance from water tariffs depends on functioning institutions.;